Rural Roadway Safety Perceptions Among Rural Teen Drivers Living in and Outside of Towns. Issue 1 (28th September 2012) - Ramirez, Marizen; Roth, Lisa; Young, Tracy; Peek‐Asa, Corinne
Abstract Purpose: To compare perceptions about rural road and general driving behaviors between teens who live in‐ and out‐of‐town from rural communities in Iowa. Methods: A cross‐sectional survey was conducted with 160 teens anticipating their Intermediate License within 3 months upon enrollment into this study. Self‐administered surveys were used to collect demographics and driving exposures (eg, frequency of driving, age when first drove unsupervised). Two Likert scales were included to measure agreement with safe driving behaviors on rural roads and general safe driving behaviors (eg, speeding, seat belt use). T‐tests were calculated comparing mean composite scores between in‐ and out‐of‐town teens, and between mean rural road and general driving safety attitude scores. A linear regression multivariable model was constructed to identify predictors of the rural road score. Results: While the majority of teens endorsed rural road and general safe driving behaviors, up to 40% did not. Thirty‐two percent did not believe the dangers of animals on rural roads, and 40% disagreed that exceeding the speed limit is dangerous. In‐town teens were less safety conscious about rural road hazards with a significantly lower mean composite score (4.4) than out‐of‐town teens (4.6); mean scores for general driving behaviors were similar. Living out‐of‐town and owning one's own car were significant predictors of increased rural road safety scores. Conclusion: Rural, in‐town teens have poorer safety attitudes about rural roadway hazards compared with out‐of‐town teens. Interventions that involve education, parental supervision, and practice on rural roads are critical for preventing teen crashes on rural roads.